1994
DOI: 10.1111/j.1600-0773.1994.tb01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a Single Oral Dose of Clobazam in Patients with Liver Disease

Abstract: The pharmacokinetic effect of a single oral in dose of 20 mg clobazam was studied in 15 patients with liver disease and in 6 healthy volunteers. Plasma concentrations of clobazam and its main metabolite, norclobazam, were measured by gas liquid chromatography. Clobazam was rapidly absorbed. Peak plasma concentrations were 350 +/- 63 ng/ml at 1.7 +/- 0.8 hr in healthy volunteers, 239 +/- 70 ng/ml at 3 +/- 1.9 hr in patients with viral hepatitis and 240 +/- 113 ng/ml at 2.5 +/- 1.5 hr in patients with cirrhosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The C max of CLB was decreased by approximately 31% in participants with chronic liver disease; however, the mean oral clearance of CLB was approximately the same between those with liver disease and healthy subjects. Furthermore, there were no significant differences in the maximum concentrations of N‐CLB between healthy subjects and patients with liver disease; even after simulation of single doses to steady state, plasma concentrations were the same for all subjects . The elimination half‐life was 2 times longer in participants with liver disease compared with healthy controls .…”
Section: Specific Populationsmentioning
confidence: 89%
See 3 more Smart Citations
“…The C max of CLB was decreased by approximately 31% in participants with chronic liver disease; however, the mean oral clearance of CLB was approximately the same between those with liver disease and healthy subjects. Furthermore, there were no significant differences in the maximum concentrations of N‐CLB between healthy subjects and patients with liver disease; even after simulation of single doses to steady state, plasma concentrations were the same for all subjects . The elimination half‐life was 2 times longer in participants with liver disease compared with healthy controls .…”
Section: Specific Populationsmentioning
confidence: 89%
“…Further information on CLB PK and PopPK modeling was identified from unpublished reports from the drug sponsor and from references cited in the articles obtained in the literature search. In total, over 100 English‐language articles and abstracts were reviewed; 53 published and 3 unpublished reports were used to compile the information presented here on CLB PK, use in specific patient populations, drug interactions, and PopPK analyses …”
Section: Clobazam Clinical Pharmacokineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…No data on co-medications in patients was provided, but the results in patients were probably contaminated by inducers. In a single-dose study, Monjanel-Mouterde et al 60 demonstrated differences in clobazam half-lives between volunteers and patients with hepatic impairment, but N-desmethylclobazam was not studied.…”
Section: Literature Reviewmentioning
confidence: 99%